1994
DOI: 10.1086/646921
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interhospital Spread of Methicillin-Resistant Staphylococcus aureus in Sao Paulo, Brazil, Using Pulsed-Field Gel Electrophoresis of Chromosomal DNA

Abstract: To evaluate the interhospital spread of methicillin-resistant Staphylococcus aureus (MRSA) clone in Sao Paulo, we analyzed the restriction fragment length polymorphisms (RFLP) of chromosomal DNA from isolates from nine Sao Paulo hospitals. Restriction digestion of genomic DNA was performed with SmaI and the fragments were separated by pulsed-field gel electrophoresis. Only six different RFLP patterns were demonstrated among 30 MRSA isolates. Isolates possessing an identical RFLP pattern were demonstrated in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 7 publications
5
48
1
9
Order By: Relevance
“…Among species of Staphylococcus, they account for 30 to 50% of nosocomial infections and this number is on the rise (2,3). After the description of the Brazilian epidemic clone (BEC) in 1992 (4), other studies further demonstrated the persistence of this microorganism in Brazilian hospitals (3). In these studies, the molecular characterization of methicillin-resistant S. aureus (MRSA) has been conducted primarily by pulsed-field gel electrophoresis (PFGE) and plasmid analysis, which showed the existence of internationally disseminated clones, reflecting epidemiological and geographical relatedness (5).…”
Section: Introductionmentioning
confidence: 99%
“…Among species of Staphylococcus, they account for 30 to 50% of nosocomial infections and this number is on the rise (2,3). After the description of the Brazilian epidemic clone (BEC) in 1992 (4), other studies further demonstrated the persistence of this microorganism in Brazilian hospitals (3). In these studies, the molecular characterization of methicillin-resistant S. aureus (MRSA) has been conducted primarily by pulsed-field gel electrophoresis (PFGE) and plasmid analysis, which showed the existence of internationally disseminated clones, reflecting epidemiological and geographical relatedness (5).…”
Section: Introductionmentioning
confidence: 99%
“…This well characterised clone has been described as ST239 when typed by Multilocus Sequence Typing (MLST) [13], and carries a type III SCCmec [14]. Previous studies [15][16][17] describing the prevalence and extension of geographic dissemination of this single MRSA clone in Brazil showed it to represent close to 80% of MRSA isolates. This clone was reported as being the most frequent among MRSA isolates recovered from several hospitals from several cities located throughout Brazil's enormous territory and separated by a distance of several thousand kilometres.…”
mentioning
confidence: 99%
“…Souza et al [11] also reported the predominance (97%) and persistence of this clone among isolates in Brazil. Using Pulsed Field Gel Electrophoresis (PFGE), the BEC has been broken down into different subtypes all related to one another [11], which could be explained by its maintenance in Brazil at least since 1990 [17].…”
mentioning
confidence: 99%
“…However, Oliveira et al (2002) described the same clone as XI::B and the HC as III::B. Nevertheless, in 1994, Sader et al (1994) had already reported the occurrence of an endemic MRSA clone in eight hospitals in São Paulo city. This was named SP Clone and was probably the first report of the BC.…”
Section: Evolution Of Typing Techniques and The Characterization Of Mmentioning
confidence: 99%